Pengaruh Strategi Operasi dan Penerapan Akuntansi Manajemen Lingkungan terhadap Inovasi Produk - Yusriadi Hala; Rostiaty Yunus; Tamsil Tamsil (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This study aims to determine the Influence of Operation Strategy and the Application of Environmental Management Accounting on Product Innovation in Food & Beverage Companies Listed on the Indonesia Stock Exchange (IDX). Data collection uses secondary data obtained from the financial statements of food and beverage companies for the 2020-2023 period. The test results of the data have been tested using the data analysis method using logistic regression techniques. The results show that partially the operation strategy has an effect on product innovation while environmental management accounting has no effect on product innovation.